Virtual Reality Pursuit: Using Individual Predispositions towards VR to Understand Perceptions of a Virtualized Workplace Team Experience - Diana R. Sanchez; Joshua McVeigh-Schultz; Katherine Isbister; Monica Tran; Kassidy Martinez; Marjan Dost; Anya Osborne; Daniel Diaz; Philip Farillas; Timothy Lang; Alexandra Leeds; George Butler; et al. (Virtual Worlds)
This study investigates how individual predispositions toward Virtual Reality (VR) affect user experiences in collaborative VR environments, particularly in workplace settings. By adapting the Video Game Pursuit Scale to measure VR predisposition, we aim to establish the reliability and validity of this adapted measure in assessing how personal characteristics influence engagement and interaction in VR. Two studies, the first correlational and the second quasi-experimental, were conducted to examine the impact of environmental features, specifically the differences between static and mobile VR platforms, on participants’ perceptions of time, presence, and task motivation. The findings indicate that individual differences in VR predisposition significantly influence user experiences in virtual environments with important implications for enhancing VR applications in training and team collaboration. This research contributes to the understanding of human–computer interaction in VR and offers valuable insights for organizations aiming to implement VR technologies effectively. The results highlight the importance of considering psychological factors in the design and deployment of VR systems, paving the way for future research in this rapidly evolving field.